The Role of Serotonin in Singultus: A Review - Petroianu, Georg A.; Lorke, Dietrich E. (Frontiers in Neuroscience, 2020)
The use of dopamine receptor blockers for chronic hiccup singultus treatment is based -at least partially- on circular thinking: chlorpromazine is FDA-approved for hiccups, chlorpromazine is a neuroleptic, neuroleptics are dopamine receptor blockers, and therefore hiccup is due to dopaminergic dysfunction. Chlorpromazine interacts with high affinity with a multitude of receptors and ion channels. This promiscuity is the basis for many of the therapeutic effects and adverse drug reactions of this drug. While an involvement of dopamine is certain, it is by no means clear that dopaminergic dysfunction is the hallmark of hiccups.singultus. The common denominator of most remedies for transient hiccup is their ability to activate the vagus nerve. Both afferent and efferent vagal activity, as well as the central integration of the Xth cranial nerve function are modulated, inter alia, via serotonergic mechanisms; beneficial (therapeutic) effects for hiccup are to be expected from serotonin (5-HT) receptor subtype ligands that enhance vagal activity. Taken together it appears that the ability to increase vagus output is mainly associated with 5-HT1A, 5-HT3 and 5-HT7 agonists and with 5-HT2C antagonists. The plausibility of the serotonergic hiccup singultus hypothesis is examined against available pharmaco-kinetic, -dynamic and clinical data for a number of drugs.